2001
DOI: 10.4049/jimmunol.166.8.5292
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Sm B Cell Differentiation in Ig Transgenic MRL/Mp-lpr/lprMice: Altered Differentiation and an Accelerated Response

Abstract: To determine the regulation of B cells specific for the ribonucleoprotein Sm, a target of the immune system in human and mouse lupus, we have generated mice carrying an anti-Sm H chain transgene (2-12H). Anti-Sm B cells in nonautoimmune 2-12H-transgenic (Tg) mice are functional, but, in the absence of immunization, circulating anti-Sm Ab levels are not different from those of non-Tg mice. In this report, we compare the regulation of anti-Sm B cells in nonautoimmune and autoimmune MRL/Mp-lpr/lpr (MRL/lpr) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 51 publications
2
37
2
Order By: Relevance
“…A similar finding was seen in mice expressing the neo-self Ag HEL in the thymus, where HEL-specific B cells were not tolerized, yet partial tolerance to HEL existed in the T cell compartment (43). In contrast to the significant B cell tolerance that exists to the lupusassociated autoantigens DNA and Sm (6,44,45), this finding suggests that even though hLa-or HEL-specific autoreactive B cells are not directly tolerized, the development of humoral autoimmunity is constrained by a deficiency of functional autoreactive Th cells. Under these circumstances, self-reactive B cells are not strictly ignorant, in that they appear to take up endogenous autoantigen constitutively and are capable of Ag presentation to T cells.…”
Section: Anti-hla B Cells and Clonal Ignorancecontrasting
confidence: 46%
See 1 more Smart Citation
“…A similar finding was seen in mice expressing the neo-self Ag HEL in the thymus, where HEL-specific B cells were not tolerized, yet partial tolerance to HEL existed in the T cell compartment (43). In contrast to the significant B cell tolerance that exists to the lupusassociated autoantigens DNA and Sm (6,44,45), this finding suggests that even though hLa-or HEL-specific autoreactive B cells are not directly tolerized, the development of humoral autoimmunity is constrained by a deficiency of functional autoreactive Th cells. Under these circumstances, self-reactive B cells are not strictly ignorant, in that they appear to take up endogenous autoantigen constitutively and are capable of Ag presentation to T cells.…”
Section: Anti-hla B Cells and Clonal Ignorancecontrasting
confidence: 46%
“…The data suggest that the maturation of hLa-specific B cells is comparable in the presence and the absence of endogenous expression of hLa autoantigen. This finding is in contrast to the anti-Sm/anti-ssDNA Tg model, where the majority of peripheral autoreactive B cells appeared to be arrested at the T-1 transitional B cell stage (4,6). Overall, therefore, the CD23 and CD24 phenotype data suggest that the presence of the hLa autoantigen in surface IgM levels were examined using three-color FACS analysis of splenic lymphocytes from anti-hLa and hLa ϫ anti-hLa Tg mice.…”
Section: Anti-hla B Cells Mature and Populate The Periphery Normally mentioning
confidence: 59%
“…A defect in the B-1 differentiation might thus be a factor in the loss of tolerance to Sm and provide insight into the low prevalence of the anti-Sm response in murine and human SLE [86]. Furthermore, manipulation of the coreceptors CD19 and CD22 in this system, confirmed that the differentiation of B-1 and tolerance is dependent on the strength of the BCR signalling.…”
Section: Role Of Polymorphism In Signalling Molecules In Determining mentioning
confidence: 54%
“…Previous studies have shown that B cells can display an activated phenotype despite being unresponsive to specific Ags in models of anergy (34,35). To investigate whether B cells expressing hCR2 adopt a similar phenotype, we examined a battery of activation markers on unstimulated B cells in the spleen and blood of hCR2-tg mice.…”
Section: Activation Markers Cd44 and Mhc Class II Are Significantly Imentioning
confidence: 99%